Rancang Bangun Aplikasi Pengelolaan Surat Ijin Tenaga Kesehatan Pada Dinas Kesehatan Kabupaten Pamekasan - Istiqomah, Belgis Medina; Nurcahyawati, Vivine; Ningsih, Norma (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
Pamekasan District Health Office is a government agency Pamekasan district in accordance with the principle of autonomy and responsible to carry out the duty of assistance in the field of Health in the district Pamekasan. Implementation of health service facilities is issued by the Health Service Division of Health Services Division and addressed to healthcare registries. The licensing certificate for health personnel is a proof that health workers have Practice and Work permits. Design of Management of Health Manpower License At Pamekasan District Health Office consists of registration of Nurse practice permit, Midwife's work permit, Doctor's license, Dental practitioner's license, pharmacist, and Pharmacist assistant. This application can also provide Hospital Information, Clinic and Puskesmas that exist in Pamekasan District. With the letter of licensing practice of web-based health workers at the District Health Office Pamekasan, expected to be a solution to the problems encountered and can generate useful information for retrieval long-term decisions as well as improving the quality of Health Services in Pamekasan District Health Office.